Complications of bariatric surgery – What the general surgeon needs to know. Issue 2 (April 2016) - Healy, Paul; Clarke, Christopher; Reynolds, Ian; Arumugasamy, Mayilone; McNamara, Deborah
Abstract: Obesity is an important cause of physical and psychosocial morbidity and it places a significant burden on health system costs and resources. Worldwide an estimated 200 million people over 20 years are obese and in the UK the Department of Health report that 61.3% of people in the UK are either overweight or obese. Surgery for obesity (bariatric surgery) is being performed with increasing frequency in specialist centres both in the UK and Ireland and abroad due to the phenomenon of health tourism. Its role and success in treating medical conditions such as diabetes mellitus and hypertension in obese patients will likely lead to an even greater number of bariatric surgery procedures being performed. Patients with early postoperative complications may be managed in specialist centres but patients with later complications, occurring months or years after surgery, may present to local surgical units for assessment and management. This review will highlight the late complications of the 3 most commonly performed bariatric surgery procedures that the emergency general surgeon may encounter. It will also highlight the complications that require urgent intervention by the emergency general surgeon and those that can be safely referred to a bariatric surgeon for further management after initial assessment and investigations.